ALGORITHM FOR MONITORING THE TOTAL AMOUNT OF DAIRY PRODUCTS IN FARMS - Safarov Elyorbek Khasanovich; Kenjaboyev Farxodbek Muxammadsulton ugli (European Science Publishing, 2024)
This article describes the technological process of milking-on-milking farms. The current state and level of process automation is analyzed. As a result of the analysis, a project structure was proposed to improve the technological process of milking. According to the project, a system control algorithm was developed, as a result of which it was stated that it is possible to automatically monitor the amount of milk being milked in farms.
Keywords: Milk products, milking, mastitis, automatic monitoring.